Building institutional capacity for a future health workforce. The WHO Global HRH Strategy. (13th November 2019) - Jacob, G
Abstract: Background: There is a growing recognition that the main population health challenges of sustaining universal healthcare coverage (UHC), and responding to the growing non-communicable diseases (NCDs) burden in all countries of the WHO European Region requires that each Member State has an effective, responsive and adaptive approach to human resources for health (HRH). However, there is a worldwide shortage of health workers and the situation is becoming more challenging globally and regionally. This presentation introduces the WHO Framework for Action, which builds on the Global Strategy on Human Resources for Health: Workforce 2030. The aim is to provide guidance to health policymakers, planners, analysts and others with a responsibility for health workforce issues. Methods: The WHO Global Strategy was adopted in 2018 by the 69th World Health Assembly. It has identified four strategic objectives, which have been adapted to the regional context as follows: to transform education and performance, to align planning and investment, to build capacity, and to improve analysis and monitoring. Results: The WHO Regional Office for Europe is working with Member States across the Region and supporting efforts to achieve sustainable health workforces. This includes promoting the use of the Labour Market Framework approach and maximising the utility of the National Health Workforce Accounts for national use and as a contributor to sustainable human resources for health planning. Conclusions: Having a sustainable health workforce in place with the right skills and competencies is critical to making progress towards achieving UHC. Effective implementation of a labour market framework approach, including multisectoral workforce governance, can support effective, responsive and adaptive approaches to human resources for health.